Microscopic Thyroidectomy: A Prudent Option - Kumar, Amit (Indian J Otolaryngol Head Neck Surg, 2018)
Microscopic Thyroidectomy is not a new surgical technique but it is not explored much. The routine use of microscope in thyroid surgery can reduce the rate of nerve palsy and hypocalcemia. Nine cases were done exclusively with the microscope only and postoperative nerve palsy and hypocalcemia were noted. We have also discussed about optimum working distances and magnification for critical structures during thyroid surgery. No patient has any nerve palsy while one patient reported transient hypocalcemia. Recurrent laryngeal nerve could be identified at 2 × but optimal magnification for dissection of nerve should be 4 ×. We find this technique easy to adopt and critical structures can be identified and preserved easily with microscopic thyroidectomy then conventional and loupe technique. It is better to have standardized and optimum working distance and magnification during different steps of surgery. It is great teaching tool in view of its better illumination and magnification.